(untitled) (Revista de Ciências Agroveterinárias, 2005)
The objective of this study was to construct and evaluate a cups anemometer (prototype) with digital readings of instantaneous, average and maximum wind speeds, using cheap and easy building materials. The prototype sensor is compound of three ladles fixed to a rotor mounted on a spindle free. The gauge consists of a permanent magnet, where a spindle rotates the pole. This produces a variable magnetic field, which indicates directly the wind speed in a crystal liquid display. The prototype calibration was performed in the laboratory, at a wind tunnel, comparing its speed with values measured by a highly accurate standard anemometer. The results showed that the prototype presented a starting speed of 0.70 m.s-1 and the digital measure presented sensibility for speedreadings above 0.85 m.s-1. There were no differences (P<0.05) between the wind speeds measured with the prototype and the standard anemometer.